Partiality towards women of color because of their gender role in Roque Moreno by Teresa González de Fanning - Santoni Morro, Isis A. (El Palma de la Juventud, 2022)
This article will analyze the biased position that the writer Teresa González de Fanning has with her character Chavelita, who is a woman of color that is part of the nineteenth-century novel Roque Moreno. We propose that this bias is because Chavelita fulfills the feminine-domestic ideal that the writer defended and professed from her position as an enlightened woman.